If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -106 = -1 + -7(-6p + 3) Reorder the terms: -106 = -1 + -7(3 + -6p) -106 = -1 + (3 * -7 + -6p * -7) -106 = -1 + (-21 + 42p) Combine like terms: -1 + -21 = -22 -106 = -22 + 42p Solving -106 = -22 + 42p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-42p' to each side of the equation. -106 + -42p = -22 + 42p + -42p Combine like terms: 42p + -42p = 0 -106 + -42p = -22 + 0 -106 + -42p = -22 Add '106' to each side of the equation. -106 + 106 + -42p = -22 + 106 Combine like terms: -106 + 106 = 0 0 + -42p = -22 + 106 -42p = -22 + 106 Combine like terms: -22 + 106 = 84 -42p = 84 Divide each side by '-42'. p = -2 Simplifying p = -2
| x+2/3x+5=(1/4) | | 3(y-3)-1=-5(-3y+4)-8y | | (x+2/3x+5)=(1/4) | | 155-2q=1 | | 4/3+1/2t=9 | | 5p+7=7-4p | | .04(y-8)+.06y=.14y-.01(10) | | 2x-3(3x+4)=8 | | 5t+1/5=t+9/10+t-7/10 | | 6/x=12 | | p^2+6p+3=0 | | 8(7-p)-8=-16p(p-2) | | x^2-5xs-24s^2= | | 14n-3(2n+6)-(n-12)=1/2(4n-36) | | (x-7/x)=(2/9) | | 8-8y=-x | | -8y+7=-9y+6 | | 0.50(x+80)+0.50x=65 | | 8(7-p)-8=-18p(p-2) | | x^4+13x^3+42x^2+10x=0 | | -7(x+1)=x-2+2(3x+1) | | 6-(2y-6)=3-3y | | 2/3x=(3/4x)+33.75 | | (x-2/x)=(7/9) | | 4v-8=-5+7v+v+1 | | 3x+5*6=48 | | (4x/4)=(9/2) | | 20x+17x-24= | | -2(3v-7)+9v=9+5(3v-2) | | (x/8)=(8/32) | | -0.10(19)+0.35x=0.05(x-14) | | 2/3x=3/4x+(135/4) |